Development of Augemted Reality Edu-Spinner to Enchance Cultural Diversity of Grade V Elementary School Students - Sonia, Fadiya Efi; Widodo, Susilo Tri (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2026)
This study was motivated by the suboptimal implementation of the “Keragaman Budaya Indonesiaku” (My Indonesian Cultural Diversity) learning material at SD Negeri Bringin 02 due to limited technological facilities and a lack of variation in instructional media. The learning process was still dominated by the Problem Based Learning (PBL) model, utilizing simple media such as pictures, with technology use limited to PowerPoint, Kahoot, and Quizizz. This study aimed to develop and examine the feasibility and effectiveness of an Augmented Reality (AR)-based Edu-Spinner learning media for fifth-grade students. The study applied a Research and Development (R&D) methodology utilizing the ADDIE model combined with a mixed-methods approach through a one-group pretest–posttest design. The participants involved were 28 students. The validation findings showed that the developed media was rated as “very good,” achieving a score of 92% from the media expert and 88% from the material expert. Furthermore, the effectiveness analysis using the Paired Sample T-Test produced a significance value of 0.00 < 0.05, which demonstrates a significant difference between the pretest and posttest scores. The N-Gain result of 0.7634 fell into the high category. Thus, the AR-based Edu-Spinner media is deemed valid and effective in enhancing students’ learning outcomes on the topic “Keragaman Budaya Indonesiaku.”